2015
DOI: 10.1214/15-sts526
|View full text |Cite
|
Sign up to set email alerts
|

A Population Background for Nonparametric Density-Based Clustering

Abstract: Despite its popularity, it is widely recognized that the investigation of some theoretical aspects of clustering has been relatively sparse. One of the main reasons for this lack of theoretical results is surely the fact that, whereas for other statistical problems the theoretical population goal is clearly defined (as in regression or classification), for some of the clustering methodologies it is difficult to specify the population goal to which the data-based clustering algorithms should try to get close. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…These issues have pushed statisticians to interact with other seemingly unrelated branches of Mathematics, like Computational Geometry, Morse Theory or Algebraic Topology, which have revealed themselves as very useful to develop some modern statistical techniques. For instance, Morse Theory (a branch of Differential Topology) was essential to provide a very precise definition for the ideal population goal of modal clustering in Chacón (); the persistence diagram was borrowed from Computational Geometry to distinguish true from spurious modes in Fasy et al (), and the concept of persistent homology from Algebraic Topology is fundamental for modern Topological Data Analysis (Wasserman, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues have pushed statisticians to interact with other seemingly unrelated branches of Mathematics, like Computational Geometry, Morse Theory or Algebraic Topology, which have revealed themselves as very useful to develop some modern statistical techniques. For instance, Morse Theory (a branch of Differential Topology) was essential to provide a very precise definition for the ideal population goal of modal clustering in Chacón (); the persistence diagram was borrowed from Computational Geometry to distinguish true from spurious modes in Fasy et al (), and the concept of persistent homology from Algebraic Topology is fundamental for modern Topological Data Analysis (Wasserman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Chacón () showed that this approach can also be formulated in terms of the domains of attraction of the density modes (hence the name of modal clustering): given xdouble-struckRd, consider the path starting at x that follows the direction of steepest ascent (which is determined by the density gradient f); such a curve γx:double-struckRdouble-struckRd is the solution to the initial value problem γxfalse(tfalse)=f()γxfalse(tfalse) with γxfalse(0false)=x. Under certain regularity conditions, that path always finishes at a critical value of f, so that f()limtγxfalse(tfalse)=0 and, therefore, the set of points x whose final destination is a given critical point is called the domain of attraction of that critical point.…”
Section: Modal Clusteringmentioning
confidence: 99%
“…Proof of Theorem 1. From Theorem 4.1 in [3] it follows that, with probability one, there exists Proof of Lemma 1. From ψ(µ, σ 2 ) = σψ(µ/σ, 1), it suffices to show that ψ(u, 1) ≤ (2/π) 1/2 + (2π) −1/2 u 2 for u ≥ 0.…”
Section: A Proofsmentioning
confidence: 98%
“…Another density clustering method is mode clustering (Chacón et al, 2015(Chacón et al, , 2013Chacón, 2012;Li et al, 2007;Comaniciu & Meer, 2002;Arias-Castro et al, 2015;Cheng, 1995). The idea is to find modes of the density and then define clusters as the basins of attraction of the modes.…”
Section: Mode Clustering and Morse Theorymentioning
confidence: 99%